Morbidity profile of outdoor patients attending an urban health training center of South Andaman district, India - Gaur, Bhanu Pratap Singh; Paul, Swapan Kumar; Pegu, Bhabani (International Journal Of Community Medicine And Public Health, 2016)
Background: The study in terms of pattern of illness and seasonal variation in a defined region is an important way to improve the quality of health services delivered to the community. The study objective was to describe the morbidity profile of patients attending the outpatient department (OPD) of urban health and training centre (UHTC) under the Dept. of Community Medicine of a teaching hospital during the year. Methods: This retrospective cross-sectional study was conducted for the duration of one year. The Data were collected from the OPD registers of medical officers from January 2015 to December 2015. Patients who had come to the centre for follow up visits were excluded from the study. Results: A total of 74,276 patients were included in the study after exclusion (39,627 males and 34,649 females). Adults (>14 years) constituted about 79.19%. Overall, respiratory disorders were the major complaints (17.17%), followed by external causes of morbidity and digestive disorders. In case of children, major diseases were wound injury, malnutrition, diseases of ear, nose and throat and skin infection. The prevalence of diseases like hypertension and diabetes were reported less in this study. Conclusions: The study gives an outline of the morbidity profile of patients attending an urban health training centre over a period of one year. This knowledge would help the health care providers and administrators to plan and deliver, enhanced and high quality services as per the community need.